The Child Is Capable: Anishinaabe Pedagogy of Land and Community - Peltier, Sharla Mskokii (Frontiers in Education, 2021)
Situated within a post-Truth and Reconciliation Commission Canadian context, educators are seeking Wisdom to create space in schools for Indigenous Knowledges, perspectives, languages and histories. An Anishinaabe scholar invites readers to make meaningful connections to knowledge from experience that centres the child within the context of an Anishinaabe summer harvest camp, a competition Powwow, and a smoke house. The storyteller takes an inward turn, exploring features of the communal learning process conducive to the learning spirit, self-evaluation and participation in learning and teaching that matches one's readiness and skill. Story is powerful for connecting the heart and mind, stimulating receptivity to assessment-making opportunities for teachers that are relevant to Indigenous student community teaching-learning traditions. True to story-telling method, the stories here are meant to stimulate remembering, reflection and a process of deep knowing. The author invites educators to think with the stories for inspiration toward personal possibilities of praxis. Positive educational transformation is set into motion as teachers connect with Indigenous peoples to honor the diversity of children, co-create a relational curriculum inclusive of family and community to embrace Indigenous Knowledge that comes from the Land, and create space to generate and transmit new knowledge through story.